The Influence of Work Discipline on Teacher Work Effectiveness with Organizational Commitment as an Intervening Variable in the Islamic Education Section Dairi Regency Ministry of Religion Office - Junita Padang; Kiki Farida Ferine (Lafadz Jaya Publisher, 2023)
Human Resources (HR) are a central factor in an educational institution. However, the fundamental phenomenon that currently tends to occur in educational institutions is the existence of educators and education personnel (HR) who are less qualified. National education has not been able to create superior human resources, both in terms of intellectuality, morality and spirituality. This type of research is quantitative, this research was conducted at the Dairi Regency Ministry of Religion Office, the research population was 275 and used the Slovin technique to draw samples, the samples taken were 163 employees. Data collection was carried out by distributing questionnaires and the research model used is analytical skill and smart PLS is the measuring tool. The results of this research are as follows: Work Discipline has a positive and significant effect on Teacher Work Effectiveness. Work Discipline has a positive and significant effect on Organizational Commitment. Organizational Commitment has an insignificant negative effect on Teacher Work Effectiveness. Work Discipline has a negative and insignificant effect on Teacher Work Effectiveness through Organizational Commitment.